Implications of Screening Blood Donors for Selected Transfusion-Transmissible Infections (TTIs): Compromise in Blood Safety? - Igbe Mba Ikwoegbu1,2* Adepoju Emmanuel-Funsho1,3, Babajimi-Joseph Amarachi1,4, Samson Elujoba1,5, Adamu Ibrahim1,6, Muhibi A. Musa1 (Sokoto Journal of Medical Laboratory Science)
Blood transfusion is a life-saving medical procedure used to replenish blood loss or treat blood disorders. However, the potential transmission of transfusion-transmissible infections (TTIs) poses a significant risk to recipients. Screening donated blood for TTIs is a cornerstone of ensuring blood safety. This article explores the implications of screening for selected TTIs, examining the potential for compromise in blood safety. It analyzes the benefits of comprehensive screening against the challenges of resource limitations, test limitations, and the ethical considerations of donor deferral. The article also discusses emerging TTIs and the evolving landscape of blood screening practices. Finally, it proposes strategies to optimize blood safety while navigating the complexities of selective screening.